BINCANG SYARIAH IN CAFES: EVALUATING SATISFACTION AND IMPACT ON ISLAMIC LITERACY DURING RAMADHAN - Syah Awaluddin; Abubakar Kabakoran; Mar’atun Shalihah; Ahmad Lonthor; Evy Safitri Gani; Didin Bahruddin; Farid Naya (Pedagogic Research-Applied Literacy Journal, 2025)
An innovation in Islamic teaching and preaching, the "Bincang Syariah" Program in Cafes aims to increase Islamic literacy in the community throughout the month of Ramadan. With a focus on young adults and professionals, this program aims to establish a casual and welcoming environment for discussing Islamic law, social concerns, and economics. The implementation strategy involves engaging conversations, brief lectures, and Q&A sessions with academic and Islamic practitioners in cafés. Surveys of participant satisfaction and an examination of the program's influence on their comprehension are used to gauge its efficacy.The program effectively raised participant interest in Islamic studies and broadened access to Islamic literacy in informal public settings, according to the evaluation's findings. This initiative shows that creative delivery techniques may be a successful substitute for community service projects by using a flexible, community-based approach to preaching.